Animal Characters in the Novel Crobinhoodovi by Dunja Kalilić. On the Trail of Stereotypes - Ślawska, Magdalena (Poznańskie Studia Slawistyczne, 2021)
This article analyses how animal characters were presented in the novel Crobinhoodovi by Dunja Kalilić, which belongs to the trend called ratni dječji roman in Croatian literature and shows the Serbian aggression against Croatia. The attention was paid in particular to the issue of stereotypes. The work consists of six parts. The first one is dedicated to the development of Croatian children’s animal studies. The second part shows the ways of portraying the war in Croatian literature for the youngest. The third part focuses on stereotypes about animals, the fourth one describes the stereotypical images of animals and people presented in the writer’s work, and the fifth part deals with national stereotypes. The last part is a summary of the considerations and presents the conclusion that the novel Crobinhoodovi makes it a goal to properly shape the child’s worldview, which is achieved by building and consolidating the negative stereotype of the Serbian soldiers.